Regional gravity field changes before and after the Menyuan MS 6.9 earthquake in 2022 and the Jishishan MS 6.2 earthquake in 2023 - Yang, Xiong; Zhao, Yunfeng; Wei, Shouchun; Zhu, Yiqing; Liang, Chenhao; Kang, Shuai; Lv, Hongbin (Frontiers in Earth Science, 2025)
The gravity changes images of different spatiotemporal scales in the region were obtained using gravity data in the Northeastern Tibetan Plateau from 2018 to 2024. By combining regional tectonic distribution and dynamic environmental, we conducted an in-depth analysis of the dynamic relationship between gravitational spatiotemporal dynamic changes and the incubation processes of the 2022 Menyuan MS 6.9 earthquake and the 2023 Jishishan MS 6.2 earthquake. The following conclusions were reached: (1) The spatial distribution of the gravitational field in the study area is closely related to the fault zones of the two earthquakes, reflecting that the fault zones underwent tectonic activity or deformation that caused changes in surface gravity during the earthquake incubation period. (2) The reverse change of gravity may be a precursor phenomenon to earthquakes, and gravity evolution images shows that both the Menyuan earthquake and the Jishishan earthquake occurred during the periods of reverse change of gravity. (3) The gravity changes gradient zone and the center of the four-quadrant are the transition region of material conversion, where the difference movement of material increase and decrease is strong, which is prone to produce shear stress and rupture, thus inducing earthquakes, and the 2022 Menyuan earthquake and the 2023 Jishishan earthquake both occurred on the high-gradient zone. (4) The significant gravity changes before and after the Menyuan earthquake and the gravity changes before the Jishishan earthquake reflect a strong correlation with deep material structural movements, which may indicate that the occurrence of the Menyuan earthquake may have influenced the occurrence of the Jishishan earthquake. Before the earthquakes, the China Earthquake Administration made mid-term predictions for Menyuan and Jishishan based on changes in the gravity field. The occurrence of these two earthquakes strongly supporting the unique role of mobile gravity field data in determining the location of strong earthquakes.